Expression of glucocorticoid inducible genes is associated with reductions in cornu ammonis and dentate gyrus volumes in patients with major depressive disorder. (25th November 2014) - Frodl, Thomas; Carballedo, Angela; Frey, Eva-Maria; O'Keane, Veronica; Skokauskas, Norbert; Morris, Derrek; Gill, Michael; Hughes, Martina Mary; Harkin, Andrew; Connor, Thomas
Abstract: Alterations of the glucocorticoid system and of hippocampal volumes have consistently been reported in patients with major depressive disorders (MDD). The aim of the present study was to investigate whether the messenger RNA (mRNA) expression of glucocorticoid inducible genes is associated with changes in the cornu ammonis (CA) and dentate gyrus subfields. Forty-three patients with MDD and 43 healthy controls were recruited and investigated with high resolution magnetic resonance imaging. Hippocampal subfields were measured using freesurfer. Measurement of whole blood mRNA expression of glucocorticoid inducible genes serum and glucocorticoid-regulated kinase 1 ( SGK1 ), FK506 binding protein 5 ( FKBP5 ), and glucocorticoid induced leucine zipper ( GILZ ) was performed. Patients with MDD had significantly smaller volumes of CA1, CA2/3, CA4/DG, and subiculum compared to healthy controls. In the regression analysis, the factor diagnosis had a significant moderating effect on the association of SGK1 and hippocampal volumes. Patients with low expression of SGK1 had significantly smaller CA2/3 and CA4/DG volumes compared to patients with high expression of SGK1 mRNA and to healthy controls with low/high expression of SGK1, respectively. Therefore, a lack of mRNA expression of glucocorticoid inducible genes in patients with MDD that seems to correspond to a blunted cortisol response is associated with smaller hippocampal CA and dentate gyrus volumes. SGK1 seems to be particularly relevant for stress-related mental disorders.